A Building Partner Capacity Assessment Framework Tracking Inputs, Outputs, Outcomes, Disrupters, and Workarounds - Paul, Christopher (RAND Corporation, 2015)
The Department of Defense conducts an assortment of building partner capacity (BPC) efforts. The needs and existing capabilities of various nations differ, however, as will results. Planning for each BPC effort carefully, assessing progress while the effort is in progress, and assessing results are all important to ensure that it meets U.S. goals and partner expectations. This report presents a framework intended to aid all these steps.